Variability Studies in Melon (Cucumis melo.L) F2 Population of Kashi Madhu x COHB38 for Powdery Mildew Resistance - Kavya, K.R.; Shivapriya, Manchali (International Journal of Applied Sciences and Biotechnology, 2019)
The present investigation was carried at College of Horticulture, Bengaluru. Evaluation of melon F2 population (Kashi Madhu X COHB38) was conducted during rabi 2016 for resistance to powdery mildew disease under natural field condition. Percent Disease Index (PDI) and AUDPC (Area Under Disease Progress Curve) value was calculated to assess the reaction of F2 (Kashi Madhu X COHB38) segregating population of melon along with the parents (COHB38 and Kashi Madhu) and F1. Based on PDI for powdery mildew disease, 152 F2 plants were classified into different categories. Twenty five F2s were resistant (0-25% PDI), 27 were moderately resistant (25.1-40% PDI), 88 were susceptible (40.1-60% PDI) and 12 F2s were highly susceptible (>60% PDI). Among 152 F2 plants, F2 -34 was found to be highly resistant with zero PDI and zero AUDPC value (no disease) followed by F2- 46 and 92 with PDI of 13.89 % and 16.11 % and 46.94 and 55.00 AUDPC value, respectively. The PDI of the disease showed a continuous distribution from highly resistant to highly susceptible phenotypes, without showing any typical segregation pattern. Int. J. Appl. Sci. Biotechnol. Vol 7(4): 407-413